THE DILLEMAS OF MULTILINGUALISM IN IRAN - Reza Kalantari (English Review: Journal of English Education, 2012)
Abstract: Iran is a multilingual country with linguistic and cultural diversity.Â Minority languages such as Turkish, Kurdish, Baluchi and Arabic are spoken inÂ Iran which constitutes part of the culture and ethnic identity. Iranian community isÂ dominantly a bilingual community. Persian as an ofï¬cial language used as linguisticÂ and cultural homogenization while minority languages are not used in educationÂ system. The controversy bilingual education and programs to serve language minorityÂ students is complex and puzzling for education authorities. On the other hand one of theÂ challenges Iranian faces is how to reconcile conï¬‚icting perspectives of bilingual educationÂ regarding globalizing of English.Â Currently, most of parents prefer their children toÂ learn English as it is the language of business, aviation and scientiï¬c research. InÂ contrast according to Iranâ€™s comprehensive scientiï¬c plan, PersianÂ should be scientiï¬clanguage of the world in the near future.Â In this research, challenges, perspectivesÂ and solutions of bilingual education in Iran were analyzed. The results indicate thatÂ conï¬‚icting of minority, majority and international language is an important challengeÂ and developing,Â promotion and expansion of Persian is a future outlook. FurthermoreÂ some suggestions and solutions to reconcile bilingual education were made.Â Keywords: bilingual education, minority, majority and international language.